Establishing the optimal number of passes during EUS-FNB for diagnosis of pancreatic solid lesions: Prospective multicenter study - Mangiavillano, Benedetto; Facciorusso, Antonio; Di Matteo, Francesco Maria; Barbera, Carmelo; Larghi, Alberto; Rizzatti, Gianenrico; Carrara, Silvia; Lisotti, Andrea; Fusaroli, Pietro; De Luca, Luca; Di Leo, Milena; Conti Bellocchi, Maria Cristina; Spadaccini, Marco; Dabizzi, Emanuele; Auriemma, Francesco; Stigliano, Serena; Ramai, Daryl; Calabrese, Federica; Manfrin, Erminia; Paduano, Danilo; Hassan, Cesare; Repici, Alessandro; Crinó, Stefano Francesco (Endoscopy International Open, 2024)
Background and study aims The optimal number of needle passes during endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) is not yet established. We aimed to perform a per-pass analysis of the diagnostic accuracy of EUS-FNB of solid pancreatic lesions using a 22G Franseen needle.Patients and methods Consecutive patients with solid pancreatic lesions referred to 11 Italian centers were prospectively enrolled. Three needle passes were performed; specimens were collected after each pass and processed individually as standard histology following macroscopic on-site evaluation (MOSE) by the endoscopist. The primary endpoint was diagnostic accuracy of each sequential pass. Final diagnosis was established based on surgical pathology or a clinical course of at least 6 months. Secondary endpoints were specimen adequacy, MOSE reliability, factors impacting diagnostic accuracy, and procedure-related adverse events.Results A total of 504 samples from 168 patients were evaluated. Diagnostic accuracy was 90.5% (85.0%–94.1%) after one pass and 97.6% (94.1%–99.3%) after two passes (P=0.01). Similarly, diagnostic sensitivity and sample adequacy were significantly higher adding the second needle pass (90.2%, 84.6%–94.3% vs 97.5%, 93.8%–99.3%, P=0.009 and 91.1%, 85.7%-94.9% vs 98.2%, 95.8%–99.3%, P=0.009, one pass vs two passes, respectively). Accuracy, sensitivity, and adequacy remained the same after the third pass. The concordance between MOSE and histological evaluation was 89.9%. The number of passes was the only factor associated with accuracy. One case of mild acute pancreatitis (0.6%) was managed conservatively.Conclusions At least two passes should be performed for the diagnosis of solid pancreatic lesions. MOSE is a reliable tool to predict the histological adequacy of specimens.
Keywords: Pancreas; Endoscopic ultrasonography; Fine-needle aspiration/biopsy